Nonlinear dynamics : from lasers to butterflies : selected lectures from the 15th Canberra International Physics Summer School, Australian National University, 21 January-1 February 2002 - Canberra International Physics Summer School (15th : 2002 : Australia); Ball, Rowena; Akhmediev, Nail N. (Singapore : World Scientific, 2003)
40